Current regulatory approaches of bioequivalence testing - Karalis, Vangelis; Macheras, Panos (EXPERT OPINION ON DRUG METABOLISM & TOXICOLOGY, 2012)
Introduction: Nowadays, reducing medication costs is vital for health care agencies. Prescription of generic drug products can help lower these expenses. A generally accepted assumption is that therapeutic equivalence, between a generic and a brand-name medication, can be claimed if bioequivalence is demonstrated. Areas covered: This article reviews the current regulatory procedures on bioequivalence testing. Special focus is placed on the guidelines recommended by the European Medicines Agency and the US Food and Drug administration. The authors also describe the evolution of these issues and the alternatives proposed in the literature. Expert opinion: Defining bioequivalence, as the condition of no significant differences in the extent and rate of absorption between the generic and the brand-name medication, sounds simple. However, the scientific and regulatory basis of bioequivalence appears rather complicated in practice. Even though the regulatory authorities have elucidated many issues, several aspects of bioequivalence assessment are still unresolved. Examples, of these open questions, in bioequivalence, include the assessment of complex drugs, such as biologics and iron-carbohydrates, the assessment of immunosuppressive agents as well as the role that pharmacogenomics plays in bioequivalence.
Keywords: bioequivalence; biowaivers; complex drugs; European Medicines Agency; Food and Drug Administration; regulatory guidelines; scaled bioequivalence approach